Cardiovascular Abnormalities in Critically Ill Leptospirosis Patients at UNS Hospital: A Study Over A 5-Year-Period - I Made Adi Palguna Rama Daffa; Risalina Myrtha; Nurhasan Agung Prabowo; Evi Liliek Wulandari (Gema Lingkungan Kesehatan, 2025)
Leptospirosis is a globally prevalent zoonotic disease. Cardiovascular involvement in leptospirosis patients, while reported, remains underexplored, especially in Indonesia. This study aims to characterize cardiovascular abnormalities in leptospirosis patients at UNS Hospital over a 5-year period. A descriptive analytical study with a retrospective approach was conducted on 38 patients aged ≥18 years who met the inclusion criteria of confirmed leptospirosis, electrocardiography (ECG) data, and hospitalization at the UNS Hospital. The data were analyzed based on ECG abnormalities. Of the 38 patients, 39.5% had sinus tachycardia, 31.6% sinus rhythm, and 2.6% each experienced supraventricular tachycardia, atrial flutter, or accelerated junctional rhythm. Furthermore, 15.8% had 1st degree AV block and 5.2% had paroxysmal atrial fibrillation. Hypotension was observed in 34.2%, while 92.1% of patients showed elevated urea levels, indicating renal involvement. The SPiRO score categorized 92.1% as severe leptospirosis cases. Mortality reached 42.1%, with ECG abnormalities present in 75% of deceased patients. These findings highlight the predominance of sinus tachycardia and the frequent co-occurrence of hypotension, renal impairment, and severe disease. This study emphasizes the critical role of early detection and monitoring of cardiovascular and hemodynamic parameters in leptospirosis patients. These findings provide valuable insights for improving diagnosis and management strategies, particularly in resource-limited settings.